Position paper: Using EdTech to support teacher education and professional development in low- and middle-income countries (internal working paper). - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2020)
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF

Problem Analysis. A Global Public Good produced by the EdTech Hub - Hennessy, Sara; Jordan, Katy; Haßler, Björn; Hollow, David; Brugha, Meaghan; Jamieson Eberhardt, Molly; Sabates, Ricardo (EdTech Hub, 2020)
An output by the EdTech Hub - #EdTechHub, https://edtechhub.org
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The relationship between educational television and mathematics capability in Tanzania - Watson, Joseph; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2020)
Previous studies have frequently demonstrated that educational television viewing can have a positive effect on learning in low-income country contexts when shows are delivered in controlled settings. However, the consequence of day-to-day viewing in such contexts has scarcely been considered. Additionally, no recent published research has provided any information on the costs of educational television. The lack of research in these areas is striking. Examining educational television viewing in monitored settings provides limited information on the influence of routine television consumption. Further, the broad reach of numerous educational television programmes should provide low perviewer costs and, resultantly, strong cost-effectiveness findings. This PhD study therefore examined (1) the association between educational television exposure and mathematics capability and (2) the cost effectiveness of educational television interventions. To achieve this, research was carried out that centred on Ubongo Kids – a popular Tanzanian-produced show delivering mathematics-focused content.
Keywords: Tanzania; ___working_potential_duplicate; cost effectiveness; educational television; mathematics; ⛔ No DOI found

OER4Schools: Outcomes of a sustained professional development intervention in Sub-Saharan Africa - Haßler, Björn; Hennessy, Sara; Hoffmann, R; Makonga, Abel (Frontiers in Education, 2020)
Sustaining educational initiatives beyond short-term pilot projects is highly challenging in low-income countries. We describe the outcomes and implications of our iterative Design-Based Implementation Research conducted in Zambia. This focused on a unique, school-based, peer-facilitated professional learning programme for primary teachers: OER4Schools integrates interactive pedagogy, open digital educational resources and mobile learning. Teacher interviews carried out 18 months after a year-long intervention showed that the programme became self-sustaining; earlier participants reported further development of their interactive teaching strategies and awareness of pupil progress; recent joiners developed similarly. Roles of teachers and pupils changed and a new classroom culture emerged. The study identifies the key mechanisms involved in sustainability, including culturally sensitive and participatory development and implementation, semi-structured multimedia materials, and supportive organisational structures for sustained professional learning. Our findings are hence framed by sociocultural influences as well as the wider policy context.
Keywords: Author:Haßler; C: Zambia; Culturally responsive pedagogy (CRP); Design-based implementation research; Interactive Pedagogy; Learner-centred pedagogy; School leadership; Sustainable Development Goal (SDG) 4; Teacher Profesisonal Development; Zambia; ___working_potential_duplicate; _yl:b; dode_eth-src-dode; dode_eth-trf2-dode; school improvement; sub-Saharan Africa

Technology in education in low-income countries: Problem analysis and focus of the Hub's work - Hennessy, Sara; Jordan, Katy; Hassler, Bjoern; Hollow, David; Brugha, Meghan; Jamieson Eberhardt, Molly; Sabates, Ricardo (2020)
An output by the EdTech Hub - #EdTechHub, https://edtechhub.org